2010
DOI: 10.5194/hess-14-1715-2010
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of gravimeter observations for modelling water storage changes at the field scale

Abstract: Abstract. Water storage is the fundamental state variable of hydrological systems. However, comprehensive data on total water storage changes (WSC) are practically inaccessible by hydrological measurement techniques at the field or catchment scale, and hydrological models are highly uncertain in representing the storage term due to the lack of adequate validation or calibration data. In this study, we assess the benefit of temporal gravimeter measurements for modelling WSC at the field scale. A simple conceptu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 89 publications
0
31
0
Order By: Relevance
“…Little is known about how deep soil moisture contributes and comes into play when groundwater is replaced, mainly because deep soil moisture is impossible to measure. High-precision gravimeters do not distinguish between near-surface and deep water storage changes but record an integral signal, so that also water storage changes in the deeper vadose zone can be monitored [Creutzfeldt et al, 2010b;Jacob et al, 2010]. We found that water storage was strongly depleted by the drought and heat wave of 2003 and that it showed an inter-annual long-term memory at the Geodetic Observatory Wettzell.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Little is known about how deep soil moisture contributes and comes into play when groundwater is replaced, mainly because deep soil moisture is impossible to measure. High-precision gravimeters do not distinguish between near-surface and deep water storage changes but record an integral signal, so that also water storage changes in the deeper vadose zone can be monitored [Creutzfeldt et al, 2010b;Jacob et al, 2010]. We found that water storage was strongly depleted by the drought and heat wave of 2003 and that it showed an inter-annual long-term memory at the Geodetic Observatory Wettzell.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, we therefore derived the total water storage change from gravity residuals based on the following scheme. A hydrological and geophysical model were coupled during the inversion process [Ferré et al, 2009;Hinnell et al, 2010] outlined in the study of Creutzfeldt et al [2010b] by extending the model period to the study period of 10 years (blue line in Figure 2). In this framework, a conceptual hydrological model calculated the water storage change in the snow, soil, saprolite and groundwater storage using daily precipitation, daily reference evapotranspiration and snow height as input data.…”
Section: Gravimeter Data and Water Storage Changesmentioning
confidence: 99%
“…A novel method using temporal gravimeter to estimate water storage change (WSC) was proposed by Creutzfeldt et al (2010). The WSC was reliably estimated by combining hydrologic and gravimetric models.…”
Section: Summary Of the Special Issue Papersmentioning
confidence: 99%
“…The model-based approach uses the conceptual hydrological model of Creutzfeldt et al (2010b). The model estimates WSC using the following input data: (1) mean precipitation measured by the two gauges, (2) the reference evapotranspiration for short canopy derived from climate data, and (3) snow height.…”
Section: Other Approaches For Comparisonmentioning
confidence: 99%
“…soil moisture at a depth of 0.6 m in Table 2). The correspondence between the model-based approach and SG residuals (97 per cent of explained signal variation) is also very high, but it is problematic to interpret the internal model structure or individual parameter sets of these conceptual models in a physical way (Creutzfeldt et al 2010b). The data-based approach agrees well with the SG residuals in terms of short-term variations, but when a specific yield of 1 per cent as derived from a pump test (Creutzfeldt et al 2010a) is used, the seasonal variation of the SG residuals is underestimated.…”
Section: Comparison To Other Approachesmentioning
confidence: 99%